Experimental investigations on dry stone masonry walls - Vasconcelos, Graça (2006)
Brick unreinforced masonry walls have been widely studied both from experimental and numerical point of view, but scarce experimental information is available for dry stone masonry walls that constitute the material more frequently used in the construction of ancient historical constructions. Therefore, the present work aims at increasing the insight about the behavior of typical ancient masonry walls under cyclic loading. To attain such goal, different experimental approaches are considered: static cyclic and dynamic tests. Besides the considerable out-of-plane movements of the stones, it was found that flexural response of the walls prevails in both experimental approaches.